TRANSFORMASI SAJIAN MUSIK GAMAD DALAM KONTEKS PERTUNJUKAN MODERN OLEH GAMAD PITUAH MINANG - Tiara Diva; Uswatul Hakim (Universitas Negeri Padang, 2026)
This study examines the transformation of Gamad music presentation in modern performance contexts by the Gamad Pituah Minang Group in Padang City. Gamad music is a traditional musical form of the Minangkabau community that emerged through the acculturation of Portuguese, Malay, and Minangkabau cultures, characterized by distinctive song structures, instrumental usage, and improvised pantun. Contemporary developments have encouraged changes in the presentation of Gamad music, one of which is reflected in the practices of Gamad Pituah Minang. This research employs a descriptive qualitative method. Data was collected through literature review, observation, interviews, and documentation. Data analysis was conducted by collecting, classifying, analyzing, and drawing conclusions from the research findings. The results indicate that Gamad Pituah Minang has carried out transformations through the development of musical arrangements, the use of modern instruments, adjustments in vocal techniques, and the utilization of digital media. Nevertheless, the fundamental structure of Gamad music is maintained, resulting in a generally positive public response toward the transformations implemented by the group. These findings demonstrate that Gamad music can continue to evolve without losing its Minangkabau cultural identity.